Rescue of endogenous 30S retroviral sequences from mouse cells by baboon type C virus. - Sherwin, S A (1978)
Mus musculus SC-1 cells were infected with M7 baboon type C virus. The progeny of this infection included viral pseudotypes that contained M7 helper virus and endogenous 30S retrovirus-associated sequences derived from SC-1 cells (RAS). The RAS sequences are unrelated by nucleic acid hybridization criteria to previously described types of murine retroviruses and do not code for known murine viral structural proteins. The RAS genome is present in multiple copies in the DNA of laboratory (M. musculus) and Asian (M. caroli and M. cervicolor) mice, is expressed in the RNA of uninfected mouse cells, and can be efficiently rescued by type C, but not type B, viruses. RAS is closely related to 30S virus-associated RNA in NIH/3T3 and BALB/c JLSV-9 cells and may be analogous to the defective 30S RNA sequences found in rats.